Practitioner Review: Treatments for Tourette syndrome in children and young people – a systematic review. (2nd May 2016) - Whittington, Craig; Pennant, Mary; Kendall, Tim; Glazebrook, Cristine; Trayner, Penny; Groom, Madeleine; Hedderly, Tammy; Heyman, Isobel; Jackson, Georgina; Jackson, Stephen; Murphy, Tara; Rickards, Hugh; et al.
Abstract : Background: Tourette syndrome (TS) and chronic tic disorder (CTD) affect 1–2% of children and young people, but the most effective treatment is unclear. To establish the current evidence base, we conducted a systematic review of interventions for children and young people. Methods: Databases were searched from inception to 1 October 2014 for placebo‐controlled trials of pharmacological, behavioural, physical or alternative interventions for tics in children and young people with TS or CTD. Certainty in the evidence was assessed with the GRADE approach. Results: Forty trials were included [pharmacological (32), behavioural (5), physical (2), dietary (1)]. For tics/global score there was evidence favouring the intervention from four trials of α 2‐adrenergic receptor agonists [clonidine and guanfacine, standardised mean difference (SMD) = −0.71; 95% CI −1.03, −0.40; N  =   164] and two trials of habit reversal training (HRT)/comprehensive behavioural intervention (CBIT) (SMD = −0.64; 95% CI −0.99, −0.29; N  =   133). Certainty in the effect estimates was moderate. A post hoc analysis combining oral clonidine/guanfacine trials with a clonidine patch trial continued to demonstrate benefit (SMD = −0.54; 95% CI −0.92, −0.16), but statistical heterogeneity was high. Evidence from four trials suggested that antipsychotic drugs improved tic scores (SMD = −0.74; 95% CI −1.08, −0.40; N  =   76), but certainty in the effect estimate was low. The evidence for other interventions was categorised as low or very low quality, or showed no conclusive benefit. Conclusions: When medication is considered appropriate for the treatment of tics, the balance of clinical benefits to harm favours α 2‐adrenergic receptor agonists (clonidine and guanfacine) as first‐line agents. Antipsychotics are likely to be useful but carry the risk of harm and so should be reserved for when α 2‐adrenergic receptor agonists are either ineffective or poorly tolerated. There is evidence that HRT/CBIT is effective, but there is no evidence for HRT/CBIT alone relative to combining medication and HRT/CBIT. There is currently no evidence to suggest that the physical and dietary interventions reviewed are sufficiently effective and safe to be considered as treatments. Abstract : Tourette syndrome (TS) is a common neurodevelopmental condition affecting approximately 1% of children and young people (c. 70, 000 people age 7–17 years in England) which if untreated has a major adverse impact on mental health, social functioning and quality of life. Despite the prevalence of TS in young people being greater than diabetes and epilepsy, it remains a frequently misunderstood condition and its seriousness at a population level is typically overlooked, as evidenced by the absence of evidence‐based clinical guidelines. TS is characterised by persistent and impairing motor and vocal tics which typically emerge in childhood, run a waxing and waning course and carry on into adult life in about 30% of young people. Tics can be highly stigmatising, especially for teenagers, and often lead to bullying, peer victimisation, social exclusion, depression and self‐harm. TS is associated and frequently coexists with other neurodevelopmental and mental health conditions including ADHD (60%), anxiety disorder (40%), OCD (30%) and ASD (20%) which add to the complexity of clinical management. Evidence from this major systematic review and meta‐analysis shows that clinically effective treatments for tics in children and young people exist and include medication (e.g. α 2‐noradrenergic agonists and antipsychotics) and behavioural interventions, including exposure and response prevention, habit reversal training (HRT) and the comprehensive behavioural intervention for tics programme which combines psychoeducation with HRT. The results of this review suggest that both medication and behavioural interventions have similar efficacy (moderate effect size) in treating tics, with behavioural interventions having a more favourable adverse effect profile. When considering medication, the more favourable adverse effect profile of α 2‐noradrenergic agonists suggests that these agents should be offered before antipsychotics. However, psychoeducation and behavioural interventions are generally the preferred treatment option, particularly as first‐line interventions, by young people and their parents. Despite demonstrated efficacy, access in most healthcare systems to evidence‐based behavioural interventions for tics is extremely poor. Therefore, given the healthcare challenge of delivering behavioural interventions at scale with existing numbers of therapists and the traditional model of face‐to‐face delivery there is a pressing need to develop and evaluate digitally delivered interventions for young people with tics using a stepped‐care model of therapist support.